Candida as an innocent bystander in esophageal ulcers: A case series - Deshidi, Srinu; Mahajan, Gaurav; Guguloth, Amrutha; Kamisetty, Viswanath; Kolla, Spoorthi; Gongati, Venu; Gongala, Harshavardhan Reddy; Kante, Bhaskar; Appasani, Sreekanth (Indian Journal of Case Reports, 2025)
Esophageal ulcers are a common endoscopic finding in patients with dysphagia with a broad range of etiologies, including gastroesophageal reflux disease, drug-induced injury, infections, malignancy, corrosive ingestion, etc. Candida albicans is the most frequently implicated organism in infectious esophagitis. However, its mere presence on histopathology does not confirm causation, particularly in immunocompetent patients, where it may represent secondary colonization. We report a case series of three patients presenting with esophageal ulcers and histological evidence of Candida. In the first two cases, esophageal ulcers resulted from pill esophagitis secondary to doxycycline and non-steroidal anti-inflammatory drugs, while the third case was attributed to herpes simplex esophagitis. Although Candida/yeast was identified in esophageal ulcer biopsies of all three patients, the first two cases improved with rabeprazole and sucralfate alone. The third case did not respond to fluconazole; further evaluation confirmed herpes simplex esophagitis and improved following antiviral treatment. This case series underscores that Candida is not necessarily the primary cause of esophageal ulcers but may instead represent secondary colonization.